Study on the Effect of Phillyrin on Streptococcus suis In Vivo and In Vitro - Fangyan Yuan; Lihan Zheng; Mengzhe Wang; Wei Liu; Xiaoyue Li; Ting Gao; Rui Guo; Zewen Liu; Keli Yang; Chang Li; Qiong Wu; Jiajia Zhu; et al. (Biomolecules)
As a zoonotic pathogen, S. suis serotype 2 (SS2) can cause severe diseases in both pigs and humans, and develop resistance to antibiotics. Plant natural compounds are regarded as promising alternatives to conventional antibiotics. Phillyrin is the major bioactive components of Chinese herbal medicine Forsythia suspensa. In this study, we explored the activity and action mechanism of phillyrin against SS2. The results showed that phillyrin could disrupt membrane integrity, destroy intracellular structures, and increase the exosmosis of DNA. Results of PCR revealed that phillyrin affected bacterial-virulence-related genes’ expression levels. Meanwhile, phillyrin significantly decreased the adhesion activity, inhibited lactate dehydrogenase (LDH) secretion, and reduced biofilm formation of SS2 in Newborn pig trachea epithelial (NPTr) cells. Furthermore, phillyrin protected tight junction protein of NPTr cells from SS2. We reported that phillyrin (0.1 mg/kg) treatment after bacterial challenge significantly improved the survival rate, ameliorated pulmonary inflammation, and inhibited the accumulation of multiple cytokines (IL-1, IL-6, IL-8, and TNF-α). Molecular docking showed that phillyrin had a good binding activity with the Ala88 and Asp111 of suilysin (SLY), one of the most important virulence factors of SS2. Collectively, phillyrin possesses antibacterial and anti-inflammatory activities, and is a promising candidate for preventing SS2 infection.